Synthesis of bismuth vanadate as visible light photocatalyst - Abdullah, Abdul Halim; Mohd Ali, Norsalinda; Mohamed Tahir, Mohamed Ibrahim (Malaysian Society of Analytical Sciences, 2009)
Bismuth Vanadate (BiVO4) photocatalyst was synthesized by precipitation methods. Two different sources of bismuth namely bismuth acetate and bismuth nitrate pentahydrate were used. The bismuth solutions were mixed with ammonium metavanadate solution before being titrated against ammonium hydrogen carbonate solution. The precipitate formed using bismuth acetate (B1)was calcined at 450 oC and that of bismuth nitrate was calcined at 450oC (B2) and 300oC (B3) under air flow for 4h.The resulting powder were characterized by XRD, FESEM, IR and its surface area. XRD pattern analysis showed that all BiVO4 sample produced are of monoclinic phase and the FESEM images showed that the particles were agglomerated. The surface area of BiVO4 produced from bismuth nitrate pentahydrate was higher (3.9 m2/g) than that produced from bismuth acetate (2.7 m2/g).Photocatalytic activities of the synthesized BiVO4 were evaluated by photodegrading Methylene Blue dye (MB) under visible light irradiation. The highest photocatalytic activity was observed when using B3 as photocatalyst with percentage removal of 34%.